Routine outcome monitoring of evidence-based parenting programmes: indications of effectiveness in a community context. Issue 1 (12th March 2014) - Hurst, Alison; Price, Anna; Walesby, Rebecca; Doolan, Moira; Lanham, Wendy; Ford, Tamsin
Abstract : Purpose: – Despite an increasing policy focus, routine outcome monitoring (ROM) is not common practice in UK children's services. This paper aims to examine whether it is feasible and valid to use measures from ROM of evidence-based parenting programmes (EBPPs) to assess the impact of services and to drive service improvements through feedback mechanisms. Design/methodology/approach: – This is a secondary analysis of ROM measures collected from a London clinic offering EBPPs over five years. Demographic information from referrals was compared for attendees and non-attendees. Changes in parent reported child behaviour were measured using the Strengths and Difficulties Questionnaire (SDQ), and a Visual Analogue Scale (VAS). Findings: – No significant differences were found in socio-demographic characteristics of attendees and non-attendees. Statistically significant differences were found between pre- and post-scores on parent reported SDQ scores and VAS concerns, as well as the SDQ Added Value Score. The data collected did not allow for investigation of a dose-response relationship between the level of attendance and any improvement made. Originality/value: – This study illustrates that ROM can provide useful information about the impact of EBPPs in a particular clinical context. Demographic data could support service managers to evaluate reach and uptake while evidence of improvements can be communicated back to parents and support future funding bids. Incomplete data limited the inferences that could be drawn, and collaborations between research centres and clinics may be a way to optimise the use of ROM to drive service improvement and innovation.